(untitled) (Comparative & International Education Series, 2022)
Advising is a critical factor in helping international graduate students overcome the challenges they face when they come to the U.S. and flourish in their academic and career pursuits. The chapter provides an overview and critical examination of the literature around experiences of international graduate students studying in the U.S. and culturally responsive advising to support these students in their personal and professional development (e.g., career development, student retention, and well-being). The Model of Advising Relationship is used to map a framework in higher education. Lastly, implications for research, clinical work, and institutions are noted in the recommendation section.